2016
DOI: 10.1016/j.ejfs.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of latent fingerprints on wet non-porous surfaces with SPR based on basic fuchsin dye

Abstract: Small particle reagent (SPR) is a technique performed to detect latent fingerprints left on wet and moist surfaces based upon the reaction between fatty acid residuals present in the traces and hydrophobic tails of the specific reagent. Those tails are linked to a hydrophilic head of zinc carbonate based formulation to give coloured precipitate. In the present study, we have prepared a novel SPR formulation constituting of zinc carbonate based on basic fuchsin dye for development of latent fingerprints on wet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Intrinsic components detected in latent fingerprints have already been identified through numerous forensic studies as an important index for the development of fingerprints (Gird et al 2012;Bailey et al 2016;Ramotowski et al 2001;Rohatgi and Kapoor 2016;Bohanan 1998;Asano et al 2002;Croxton et al 2010;Stewart et al 1989;Antoine et al 2010;Michalski et al 2013a;Archer et al 2005;Cadd et al 2015a;Cadd et al 2015b). These studies showed that the components of a fingerprint are 95-99% water and organic (protein, amino acids, urea, and lipids) and inorganic (sodium, potassium, chloride, and phosphate) compounds secreted from eccrine, apocrine, and sebaceous glands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsic components detected in latent fingerprints have already been identified through numerous forensic studies as an important index for the development of fingerprints (Gird et al 2012;Bailey et al 2016;Ramotowski et al 2001;Rohatgi and Kapoor 2016;Bohanan 1998;Asano et al 2002;Croxton et al 2010;Stewart et al 1989;Antoine et al 2010;Michalski et al 2013a;Archer et al 2005;Cadd et al 2015a;Cadd et al 2015b). These studies showed that the components of a fingerprint are 95-99% water and organic (protein, amino acids, urea, and lipids) and inorganic (sodium, potassium, chloride, and phosphate) compounds secreted from eccrine, apocrine, and sebaceous glands.…”
Section: Introductionmentioning
confidence: 99%
“…Among these components, lipids, included glycerides (33%), fatty acids (30%), wax esters (22%), cholesterol esters (2%), cholesterol (2%), and squalene (10%), make up a large portion of the latent fingerprint in organic compounds (Gird et al 2012;Bailey et al 2016;Ramotowski et al 2001). These compounds originate from the sebum secreted by the sebaceous glands and are very useful ingredients to visualize fingerprints (Rohatgi and Kapoor 2016). Fatty acids are used as a particular target ingredient, which is important for aging studies due to its oxidation over time and the fact that it can be used to identify donor gender, age, eating habits, and race (Bohanan 1998;Asano et al 2002;Croxton et al 2010;Stewart et al 1989;Antoine et al 2010;Michalski et al 2013a;Archer et al 2005;Cadd et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available SPR, labeled SPR 2001, purchased from Sirchie consisted of zinc carbonate (a white powder), Tergitol‐7 (a surfactant), and water. This formulation is very similar to that reported by Rohatgi and Kapoor . This SPR was spread using an aerosol container onto the suspected surfaces.…”
Section: Introductionmentioning
confidence: 73%
“…They concluded that a sequential treatment of the samples, which involves SPR and some lysochromes, was the most appropriate for best results. Rohatgi and Kapoor replaced molybdenum disulfide in the original SPR formulation suitable for white surfaces with white basic zinc carbonate, basic fuchsin, and a commercial liquid detergent suitable for black surfaces. Commercially available SPR, labeled SPR 2001, purchased from Sirchie consisted of zinc carbonate (a white powder), Tergitol‐7 (a surfactant), and water.…”
Section: Introductionmentioning
confidence: 99%
“…Physical visualization method: powder suspension techniques Small particle reagent SPR (wet powder suspension) was introduced to visualize latent fingerprints on non-porous objects that were accidentally or deliberately wetted (Trapecar 2012;Fish et al 2014;Houck and Siegel 2015;Kasper 2016;Rohatgi and Kapoor 2016). Researchers concurrently assumed that SPR adheres to the lipid-soluble constituents of fingerprints (Lennard 2007;Daluz 2015;Houck and Siegel 2015;Bumbrah 2016).…”
Section: Developments Of Physical and Chemical Fingerprint Visualizinmentioning
confidence: 99%